Impact of aerobic and resistance exercise combination on physical self-perceptions and self-esteem in women with obesity with one-year follow-up - Megakli, T.; Vlachopoulos, S.; Thøgersen-Ntoumani, Cecilie; Theodorakis, Y. (Taylor & Francis, 2017)
The effectiveness of an exercise intervention including both aerobics and resistance training components in improving physical self-perceptions and global self-esteem (GSE) in women with obesity was examined. An experimental design with a one-year follow-up was used. Women with obesity (n = 72) participated in a structured exercise programme for 12 weeks after being randomised into a control and an exercise group. Exercise self-efficacy, body attractiveness, physical strength, sport competence, physical condition, physical self-worth, and GSE were measured at pre-intervention, early intervention, mid-intervention, immediately after the intervention, and five times following programme termination at 1, 3, 6, 9, and 12 months, respectively. Analyses of covariance revealed exercise effects for all of the dependent variables except for body attractiveness. Generally, exercise effects lasted between 6 and 12 months. A 12-week physical exercise programme including aerobic and resistance training components has the potential to improve physical self-perceptions and self-esteem in women with obesity.